2015
DOI: 10.7314/apjcp.2015.16.2.713
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Gene Polymorphisms Do Not Predict Response to Radiotherapy-Based Multimodality Treatment of Patients with Rectal Cancer: a Meta-analysis

Abstract: Background: : A number of association studies have been carried out to investigate the relationship between genetic polymorphisms in DNA repair genes and response to radiotherapy-based multimodality treatment of patients with rectal cancer. However, their conclusions were inconsistent. The objective of the present study was to assess the role of DNA repair gene genetic polymorphisms in predicting genetic biomarkers of the response in rectal cancer patients treated with neoadjuvant chemoradiation. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The AA genotype (OR = 0.52, 95% CI: 0.31–0.86, P = 0.012) was associated with a reduced risk of minor treatment response when using grade ≥3 as the cutoff value ( Table 3 ). We found that this SNP does not predict treatment response in rectal cancer, which is consistent with previous studies ( 16 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The AA genotype (OR = 0.52, 95% CI: 0.31–0.86, P = 0.012) was associated with a reduced risk of minor treatment response when using grade ≥3 as the cutoff value ( Table 3 ). We found that this SNP does not predict treatment response in rectal cancer, which is consistent with previous studies ( 16 ).…”
Section: Resultssupporting
confidence: 93%
“…However, the results are not consistent. A previous meta-analysis of four studies has stated that this SNP does not predict response to chemoradiotherapy (n = 511) in patients with rectal cancer ( 16 ). However, the sample size in genetic association studies is still too small to obtain sufficient power to a robust conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported in rectal cancer patients for ERCC1 polymorphisms and protein expression . In contrast, the prognostic value of ERCC1 rs11615 for response to FP‐based CRT was not confirmed in meta‐analysis . However, most of those results were based on retrospective and/or underpowered studies that included patients with various ethnicities and cancer stages, variable doses and schedules of FU‐based therapy and concomitant administration of various cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 56%
“…The impact of ERCC2 rs13181 and ERCC2 protein expression in response to FP‐based CRT in rectal cancer has been less extensively investigated and not identified as predictive/prognostic marker so far . In our pharmacogenetic analysis, ERCC2 rs1799787 and rs13181 were found to have both prognostic and borderline significant predictive (i.e., treatment dependent) effect on tumor response.…”
Section: Discussionmentioning
confidence: 67%
“…The impact of a set of DNA repair genetic markers (i.e., XRCC1-rs25487, XRCC1-rs179978, XRCC3-rs861539, ERCC1-rs11615, ERCC2-rs13181) on the tumor pathological response was analyzed by a meta-analysis (Guo et al, 2015), including five studies for a total of 265 Caucasian patients with LARC. The meta-analysis found no association between the polymorphisms and the response to radiotherapy in the context of LARC multimodality treatment.…”
Section: Dna Repair Pathwaymentioning
confidence: 99%